2020
DOI: 10.3389/fimmu.2020.594071
|View full text |Cite
|
Sign up to set email alerts
|

Maf1 Ameliorates Sepsis-Associated Encephalopathy by Suppressing the NF-kB/NLRP3 Inflammasome Signaling Pathway

Abstract: BackgroundThe NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome has been identified as an important mediator of blood–brain-barrier disruption in sepsis-associated encephalopathy (SAE). However, no information is available concerning the critical upstream regulators of SAE.MethodsLipopolysaccharide (LPS) was used to establish an in vitro model of blood–brain barrier (BBB) disruption and an in vivo model of SAE. Disruption of BBB integrity was assessed by measuring the expression levels of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 67 publications
0
45
0
Order By: Relevance
“…Nod-like receptor protein 3 (NLRP3) plays an important role in the inflammation cascade by amplifying the inflammation response ( Islam et al, 2020 ). Chen et al found a suppression of the NF-kB/NLRP3 inflammatory pathway by directly binding to the promoter region of NLRP3, which resulted in a decreased cell apoptosis and inflammation, and an alleviation of BBB disruption and SAE ( Chen et al, 2020 ). Kikuchi et al showed that inhibition of poldip2 could attenuate BBB disruption caused by sepsis by regulating the nuclear translocation process of NF-κB as well as Cox-2 expression, preventing the occurrence and development of SAE ( Kikuchi et al, 2019 ) ( Figure 2 ).…”
Section: Bbb and Saementioning
confidence: 99%
“…Nod-like receptor protein 3 (NLRP3) plays an important role in the inflammation cascade by amplifying the inflammation response ( Islam et al, 2020 ). Chen et al found a suppression of the NF-kB/NLRP3 inflammatory pathway by directly binding to the promoter region of NLRP3, which resulted in a decreased cell apoptosis and inflammation, and an alleviation of BBB disruption and SAE ( Chen et al, 2020 ). Kikuchi et al showed that inhibition of poldip2 could attenuate BBB disruption caused by sepsis by regulating the nuclear translocation process of NF-κB as well as Cox-2 expression, preventing the occurrence and development of SAE ( Kikuchi et al, 2019 ) ( Figure 2 ).…”
Section: Bbb and Saementioning
confidence: 99%
“…Nuclear factor-kappa B (NF- κ B) is a widely studied transcription factor that is involved in many physiological processes, such as regulating multiple aspects of innate and adaptive immune function [ 17 , 18 ], and as a key mediator of the inflammatory response in regulating inflammatory pain [ 19 ], neuropathic pain [ 20 ], and other chronic pain [ 21 ]. Recent studies have shown that NF- κ B participates in the inflammatory cascade by activating the Nod-like receptor protein 3 (NLRP3) inflammasome in the nucleus [ 22 , 23 ]. The activation of inflammasomes contributes to the development of chronic pain [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Morris water maze test was carried out to evaluate mice's neurological dysfunction as previously described [14][15][16]. The water maze consisted of a circular black pool (100 cm diameter, 38 cm deep), and it was filled with opaque water (25 cm deep).…”
Section: Morris Water Maze Testmentioning
confidence: 99%